2012
DOI: 10.5415/apallergy.2012.2.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate for acute asthma in adults: a systematic literature review

Abstract: Magnesium sulfate (MgSO4) has been considered as an adjunct therapy for severe and life-threatening asthma exacerbation. The literature search was performed using MEDLINE, EMBASE, Cochrane Library and Google Scholar to summarize the current state of knowledge regarding magnesium therapy in acute exacerbation of adult asthma. A total of 16 trials and 4 meta-analyses were identified. As results, intravenous MgSO4 was beneficial in severe exacerbation, but evidence for nebulized magnesium was insufficient. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
(46 reference statements)
4
32
0
Order By: Relevance
“…Magnesium sulfate (MgS) given as 2 grams intravenously (IV) has shown benefit and a trend for greater improvement in the symptom of breathlessness in severe acute asthma exacerbation in a number of studies [35, 36]. A recent study showed some evidence that concomitant administration of intravenous MgS combined with standard approaches diminished the need for hospitalization in acute severe asthmatic patients compared with regular treatments alone; use of concomitant MgS by nebuliser, however, did not improve outcomes and proved no better than placebo [37].…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium sulfate (MgS) given as 2 grams intravenously (IV) has shown benefit and a trend for greater improvement in the symptom of breathlessness in severe acute asthma exacerbation in a number of studies [35, 36]. A recent study showed some evidence that concomitant administration of intravenous MgS combined with standard approaches diminished the need for hospitalization in acute severe asthmatic patients compared with regular treatments alone; use of concomitant MgS by nebuliser, however, did not improve outcomes and proved no better than placebo [37].…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that magnesium induces bronchial smooth muscle relaxation in a dose-dependent manner, possibly by inhibiting calcium influx into the cytosol, histamine release from mast cells and/or or acetylcholine release from cholinergic nerve endings and by increasing the effect of β2-agonist by increasing the receptor affinity (3). These results coupled with the observation that the polymorphonuclear and erythrocyte magnesium content in asthma could be lower (though some studies disputed this) compared to control suggests that there is an important role for magnesium in the pathogenesis of asthma especially, since magnesium may serve as a natural calcium channel blocker in the release of chemical mediators (3)(4)(5). Magnesium deficiency is relatively common in USA (6,7).…”
Section: Accepted Manuscriptmentioning
confidence: 68%
“…Improved outcomes in adults and children with AEA treated with iv magnesium are reported in several systematic reviews and meta-analyses [89,90,92]. Combining iv magnesium with inhaled SABAs and systemic corticosteroids markedly improved spirometry and reduced rates of hospitalization in children and improved spirometry in adults [90].…”
Section: Magnesium Sulfatementioning
confidence: 96%
“…Possible mechanisms to explain the bronchial smooth muscle relaxation seen with magnesium include blocking calcium influx into the cytosol by and its release from the endoplasmic reticulum and activating sodium-calcium pumps [89,90]. Further, magnesium can block the interaction between calcium and myosin leading to muscle cell relaxation.…”
Section: Magnesium Sulfatementioning
confidence: 98%